CT-Quantified Adipose Tissue Distribution: Risk or Protective Factor for Complications after Rectal Cancer Surgery? - Johanna Nattenmüller; Jürgen Böhm; Astgik Bagdassarjan; Yakup Kulu; Biljana Gigic; Martin Schneider; Hans-Ulrich Kauczor; Cornelia M. Ulrich; Alexis Ulrich (Obesity Facts, 2019)
Purpose: Obesity is associated with increased incidence and mortality in rectal cancer (RC). However, an obesity paradox in the sense of a protective effect of obesity is discussed controversially. We evaluated whether adipose tissue distribution has an impact on medical (MC) and surgical complications (SC) after RC surgery. Methods: A total of 296 RC patients underwent oncological surgery and multidetector CT with quantification of total (TAT), visceral (VAT), and subcutaneous adipose tissue (SAT). Logistic regressions on SC (anastomotic leakage [n = 26], wound infection [n = 58], bleeding [n = 12], abscess [n = 32], bladder dysfunction [n = 24], burst abdomen [n = 10]), and MC (pulmonary [n = 22], cardiac [n = 18], urinary tract infection [n = 9], sepsis [n = 5]) were performed. Results: High pelvicVAT was associated with reduced risk for overall SC (OR = 0.915, p = 0.012) and anastomotic leakage (OR = 0.587, p = 0.024, CI: 0.369/0.934). In contrast, CT-quantified obesity was associated with increased risk for wound infection, bladder dysfunction, burst abdomen, overall MC, and cardiac complications (ORs up to 1.423). BMI was not associated with any SC or MC. Conclusion: An obesity paradox with a protective effect of CT-quantified adipose tissue was confirmed for anastomotic leakage and overall SC. In contrast, high adipose tissue was associated with higher risk for other SC and MC. These results show a more complex influence of body composition on MC and SC. CT-quantified obesity is able to provide deeper insights to explain the obesity paradox beyond BMI.